2022
DOI: 10.1186/s13041-022-00962-3
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of hypothalamic FGF11 prevents diet-induced obesity

Abstract: Fibroblast growth factor 11 (FGF11) is a member of the intracellular fibroblast growth factor family. Here, we report the central role of FGF11 in the regulation of metabolism. Lentiviral injection of Fgf11 shRNA into the arcuate nucleus of the mouse hypothalamus decreased weight gain and fat mass, increased brown adipose tissue thermogenesis, and improved glucose and insulin intolerances under high-fat diet conditions. Fgf11 was expressed in the NPY–expressing neurons, and Fgf11 knockdown considerably decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…CCR2 [461], FASLG (Fas ligand) [462], CD28 [463], LYZ (lysozyme) [464], CCL5 [465], CCL3 [466], C6 [467], MSR1 [468], HGF (hepatocyte growth factor) [469], VEGFA (vascular endothelial growth factor A) [470], ADM (adrenomedullin) [471], CR2 [472], MAG (myelin associated glycoprotein) [473], CDH1 [474], OLIG2 [475], SEMA4D [476], ADAMTS4 [477], BMP2 [478], ERBB3 [479] and NKX2-2 [480] have been identified as a hub gene in spinal cord injury in several studies. CCR2 [481], FASLG (Fas ligand) [286], CD24 [482], CD28 [483], LYZ (lysozyme) [484], IL7R [485], CCL5 [486], LTF (lactotransferrin) [487], GPNMB (glycoprotein nmb) [488], CTLA4 [489], IRF4 [490], CHIT1 [491], NPY2R [492], TAB2 [131], CD52 [302], CD163 [493], MSR1 [306], HGF (hepatocyte growth factor) [494], TRPM8 [495], TTR (transthyretin) [496], F13A1 [497], ADM (adrenomedullin) [498], COL9A3 [499], ANGPTL4 [500], CHI3L1 [501], BMP8A [502], SREBF1 [503], CDKN1C [504], INSIG1 [505], ATF3 [506], HK2 [507], TF (transferrin) [508], MOG (myelin oligodendrocyte glycoprotein) [509], ADAMTS4 [510], BMP2 [511], HSPA2 [512], LMNA (lamin A/C) [330], HSD11B1 [513], NKX2-2 [514], NHLH2 [433], FGF11 [515], ASPA (aspartoacylase) [336], FASN (fatty acid synthase) [516], PNPLA3 [517], MMP15 [518], CBR1 [519], LRP2 [520], WNT7A [340], GPR142 [521], GPD1 [343], LIPE (lipase E, hormone sensitive type) [522], CNDP1 […”
Section: Discussionmentioning
confidence: 99%
“…CCR2 [461], FASLG (Fas ligand) [462], CD28 [463], LYZ (lysozyme) [464], CCL5 [465], CCL3 [466], C6 [467], MSR1 [468], HGF (hepatocyte growth factor) [469], VEGFA (vascular endothelial growth factor A) [470], ADM (adrenomedullin) [471], CR2 [472], MAG (myelin associated glycoprotein) [473], CDH1 [474], OLIG2 [475], SEMA4D [476], ADAMTS4 [477], BMP2 [478], ERBB3 [479] and NKX2-2 [480] have been identified as a hub gene in spinal cord injury in several studies. CCR2 [481], FASLG (Fas ligand) [286], CD24 [482], CD28 [483], LYZ (lysozyme) [484], IL7R [485], CCL5 [486], LTF (lactotransferrin) [487], GPNMB (glycoprotein nmb) [488], CTLA4 [489], IRF4 [490], CHIT1 [491], NPY2R [492], TAB2 [131], CD52 [302], CD163 [493], MSR1 [306], HGF (hepatocyte growth factor) [494], TRPM8 [495], TTR (transthyretin) [496], F13A1 [497], ADM (adrenomedullin) [498], COL9A3 [499], ANGPTL4 [500], CHI3L1 [501], BMP8A [502], SREBF1 [503], CDKN1C [504], INSIG1 [505], ATF3 [506], HK2 [507], TF (transferrin) [508], MOG (myelin oligodendrocyte glycoprotein) [509], ADAMTS4 [510], BMP2 [511], HSPA2 [512], LMNA (lamin A/C) [330], HSD11B1 [513], NKX2-2 [514], NHLH2 [433], FGF11 [515], ASPA (aspartoacylase) [336], FASN (fatty acid synthase) [516], PNPLA3 [517], MMP15 [518], CBR1 [519], LRP2 [520], WNT7A [340], GPR142 [521], GPD1 [343], LIPE (lipase E, hormone sensitive type) [522], CNDP1 […”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, FGF11 regulated the expression of UCP1, which is located in the inner mitochondrial membrane of brown adipocytes, which can dissipate the energy stored in the mitochondrial electrochemical gradient as heat upon ATP synthesis [ 38 ]. A previous study has shown that inhibition of FGF11 in the hypothalamus prevented diet-induced obesity and enhanced BAT thermogenesis via the sympathetic nervous system [ 39 ]. In the present study, FGF11 promoted the expression of the UCP1 protein and an EBF2 element was responsible for UCP1 promoter activity.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of FGF11 can significantly reduce mesangial cell proliferation and fibrosis in the progression of diabetic nephropathy[ 50 ]. Silencing FGF11 in the mouse hypothalamus can reduce HFD-induced body weight gain and fat accumulation by increasing brown adipose tissue thermogenesis and insulin intolerance[ 51 ]. In addition, FGF-11 regulates the differentiation and thermogenesis of brown adipocytes in goats[ 52 ].…”
Section: Fgfs Play An Important Role In Diabetes and Related Diseasesmentioning
confidence: 99%